THE EFFECT OF PRODUCT QUALITY, BRAND IMAGE AND PRICE ON THE DECISION TO PURCHASE AN iPHONE (A STUDY OF STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, ISLAMIC UNIVERSITY OF SUMATERA) NORTH MANAGEMENT STUDY PROGRAM CLASS 2021) - Nola Amelia; Nilawati Nasti; Julienda Br Harahap (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The purpose of this study is to analyze and determine the extent of influence of product quality on iPhone purchasing decisions among students, the influence of price on iPhone purchasing decisions among students, and the influence of price on iPhone purchasing decisions among students. This study was conducted at the Islamic University of North Sumatra, specifically at the Faculty of Economics and Business.Business Management Study Program Class of 2021.In sampling using simple random sampling technique, with a total sample of 63 respondents. The method used in the study is the multiple linear regression analysis method. This type of research is quantitative research. The results of this study, namely: (1) product quality has a positive and significant effect on the decision to purchase an iPhone cellphone in students of the Faculty of Economics and Business, Islamic University of North Sumatra. (2) brand image does not have a positive and significant effect on the decision to purchase an iPhone cellphone in students of the Faculty of Economics and Business, Islamic University of North Sumatra. (3) price has a positive and significant effect on the decision to purchase an iPhone cellphone in students of the Faculty of Economics and Business, Islamic University of North Sumatra.